MECHANICAL PROPERTIES OF CR-DLC LAYERS PREPARED BY HYBRID LASER TECHNOLOGY - Petr Písařík; Miroslav Jelínek; Jan Remsa; Zdeněk Tolde (Acta Polytechnica CTU Proceedings)
Diamond like carbon (DLC) layers have excellent biological properties for use in medicine for coating implants, but poor adhesion to biomedical alloys. The adhesion can be improved by doping the DLC layer by chromium, as described in this article. Chromium doped diamond like carbon layers (Cr‑DLC) were deposited by hybrid deposition system using KrF excimer laser and magnetron sputtering. Carbon and chromium contents were determined by wavelength dispersive X-ray spectroscopy. Mechanical properties were studied by nanoindentation. Hardness and reduced Young's modulus reached 31.2 GPa and 271.5 GPa, respectively. Films adhesion was determined by scratch test and reached 19 N for titanium substrates. Good adhesion to biomedical alloys and high DLC hardness will help to progress in the field of implantology.